Pouch lithium-ion battery thermal management by using a new liquid-cooling plate with honeycomb-like fins - Linxiang Fu; Zhendong Zhang; Lei Sheng; Zhiwei Kuang; Zehua Zhu; Qing Bi (Case Studies in Thermal Engineering)
Excellent thermal management plays a significant role in ensuring lithium-ion batteries' performances. This work proposes a thermal control method for pouch batteries by using a cooling-plate with novel channels designed with streamlined and honeycomb-like fins. Numerically, such effects are studied as coolant mass flow, inlet temperature, cooling-plate's main channel aspect ratio, and fin spacing on the battery's thermal performance. An optimal scheme for comprehensive performance of the battery is selected by orthogonal test method. The results show that increasing coolant mass flow can suppress the battery's temperature rise. Moreover, the pressure drop of cooling-plate increases linearly. Decreasing coolant inlet temperature has a positive impact on reducing battery temperature rise and minimizing temperature difference. Increasing the main channel aspect ratio and fin spacing of cooling-plate both reduce the battery's minimum temperature, but the uniformity of coolant flow distribution is improved and deteriorated, respectively. The orthogonally optimized scheme (A5B2C2D3) can control maximum cell temperature at 27.29 °C while reducing pressure drop by up to 53.71 %. Experimental validation shows that the designed cooling-plate has excellent cooling performance, and the maximum temperature deviation is within 2.00 °C. The study would be valuable to deeply understand the thermal design progress of battery cooling-plate.